University of Malaya's electronic procurement system (UMEPS) Version 3.0 / Chia Wee Leng - Chia , Wee Leng (2001)
University of Malaya's Electronic Procurement System (UMEPS) is a project in association with the government's mission in implementing Electronic Government, one of the seven flagship applications under Multimedia Super Corridor (MSC). It involves the automation of all business processes in the university. UMEPS is a Web-based procurement system that allows the faculties or departments in the university to electronically select items to be procured, initiate an electronic approval process and also create, submit and receive purchase orders, delivery orders and other related documents electronically. The six user groups of UMEPS include requestors, suppliers, approvers, treasurers, administrators and managers. The entire system is based on a three-tier client/server architecture. All communications of the system are done via the TCP/IP protocol. This dissertation introduces the project and provides a description on the topics studied and researched during the literature review. It also extracts the findings from the requirements and analysis process for the intent of system design. Project modules specific to the development of this system include Audit Trail, Archive, Quotation Requisition, Supplier Information and Supplier Profile.